Plane modules and distributive rings - Tuganbaev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Let A be a semiprime ring entire over its center. We prove that the following conditions are equivalent: (a) A is a ring distributive from the right (left); (b) w.gl. (A) ≤ 1; moreover, if M is an arbitrary prime ideal of the ring A, then A/M is a right Ore set.